The kinase PDK1 is critical for promoting T follicular helper cell differentiation - Sun, Zhen; Yao, Yingpeng; You, Menghao; Liu, Jingjing; Guo, Wenhui; Qi, Zhihong; Wang, Zhao; Wang, Fang; Yuan, Weiping; Yu, Shuyang (eLife, 2021)
The kinase PDK1 is a crucial regulator for immune cell development by connecting PI3K to downstream AKT signaling. However, the roles of PDK1 in CD4 + T cell differentiation, especially in T follicular helper (Tfh) cell, remain obscure. Here we reported PDK1 intrinsically promotes the Tfh cell differentiation and germinal center responses upon acute infection by using conditional knockout mice. PDK1 deficiency in T cells caused severe defects in both early differentiation and late maintenance of Tfh cells. The expression of key Tfh regulators was remarkably downregulated in PDK1-deficient Tfh cells, including Tcf7 , Bcl6 , Icos , and Cxcr5 . Mechanistically, ablation of PDK1 led to impaired phosphorylation of AKT and defective activation of mTORC1, resulting in substantially reduced expression of Hif1α and p-STAT3. Meanwhile, decreased p-AKT also suppresses mTORC2-associated GSK3β activity in PDK1-deficient Tfh cells. These integrated effects contributed to the dramatical reduced expression of TCF1 and ultimately impaired the Tfh cell differentiation.